In the flesh - Kim, Jueun (Michaelis School of Fine Art, 2022)
The core difference between machines and humans is that humans have consciousness and life, albeit some machines designed and created by humanity are able to make decisions, facilitate intellectual enhancements and even develop physically. Humanity is dependent on a network of machines and technologies that transfer power to and engage with residences, industries and day-to-day activities, and as much as it is humanity that advances technology, they equally evolve with and through technology. This ever-evolving technology has become so integrated with human bodies and minds that it has a disturbing range of control over critical aspects of their lifestyles, to the point that humanity may be functionally impaired without it. Humanity has mechanised the simple act of being human but continues to build machines and develop technologies that act, look and respond in an increasingly human way. It is no longer possible for humanity to simply switch the machines off, because if they do, they may switch themselves off as well. The artworks and associated written dissertation of In the Flesh, set out to explore the sensitive symbiotic relationship between humans and the machines.